Evolution of the Complexity of Patient Care Activity in a Cardiac Intensive Care Unit - Liliana BUCUR; Viorica NEDELCU; Daniela MINCULEASA; Mihaela PODĂRĂSCU; Ştefania CĂLIN; Mihaela BRATANOF; Ioana MARINICĂ; Daniela FILIPESCU (Applied Medical Informatics, 2023)
Background and Aim: The Cardiac Intensive Care Unit (CICU) is characterized by a high level of complexity of patient care activity, which implies particular responsibilities, skills and demands for professionals in these wards. To face these challenges, effective communication is needed within the multiprofessional medical team. Materials and Methods: We carried out a retrospective study for a period of 8 years (2015-2022), and we evaluated the number of patients cared for, the reason and type of admission, the presence of complex monitoring and life support devices, the activity score for the ICU (OMEGA-RO), and the length of stay in CICU. Results: The evolution of patients from 2015-2019 showed a constant upward trend: patients cared for - from 750 to 960; surgical patients - from 346 to 595; emergencies - from 300 to 508. Also, the number of patients with complex monitoring and assistance increased constantly, from 263 to 485. A constant increase was also observed for OMEGA-RO - from 149 to 170.2 and the average length of stay - from 2.8 to 4.5 days. The impact of the COVID-19 pandemic led to a reduction in patients' access to medical services, as evidenced by the decrease in the number of patients during 2020-2021. However, the data analyzed for 2022 prove the return to the trend of increasing the number of patients and the complexity of their care. Conclusions: The high complexity of the patient care process in CICU argues for the need to ensure an optimal level of human and material resources to facilitate the provision of safe and quality care. There is also a need for the periodic participation of the staff in training programs and continuous medical education, which ensures the maintenance and development of the specific skills of the professionals in these departments.